Kimball data warehouse for the sales analysis process in a manufacturing business in Perú - Vidal Carlos, Palomino; Obregon Patricia, Condori (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
The main goal of this research is to demonstrate that the use of innovative technology like business intelligence (BI) in a specific type of business significantly impacts their sales processes, enhancing decision-making, promotional strategies, and consequently customer loyalty and sales growth. The case study is a manufacturing business located in Lima, Peru. The information requirements of this business were analyzed, and a data mart model was created using the Kimball methodology. This multidimensional model enabled the comparison of client sales trends to propose new promotions and marketing strategies. The data analysis used to evaluate the results included hypothesis testing, analysis of employee responses to questionnaires to measure the impact of technology use on sales processes, and data reviews to assess sales increases both before and after the implementation of this technology. In both cases, the approval of the BI technology by the employees was satisfactory, and the increase in sales quantity was significant.